Relationship of Controlling Negative Thoughts and Parenting Stress with Marital Satisfaction in Parents of Children with Learning Disability: Mediated by Sexual Satisfaction - Mohebbi, Zahra; Dasht Bozorgi, Zahra; Johari Fard, Reza (Advances in Nursing & Midwifery, 2023)
Abstract Introduction: Lack of satisfying sexual relations weakens marital relationships. The present study aimed to investigate the relationship between controlling negative thoughts and parenting stress with the marital satisfaction of parents of children with learning disabilities as influenced by the mediating role of sexual satisfaction. Methods: The statistical population of this descriptive correlational study covered all parents of children with learning disabilities in Tehran in 2020, 212 of whom were selected as the statistical sample using convenience sampling based on the inclusion and exclusion criteria. The research instruments included the Marital Satisfaction Scale, the Thought Control Questionnaire, the Parenting Stress Questionnaire, and the Sexual Satisfaction Questionnaire. Descriptive statistics including mean and standard deviation as well as Pearson’s correlation coefficient were used for data analysis. The proposed model was evaluated using structural equation modeling (SEM) via SPSS-25 and AMOS-25 software. Results: The results showed that the correlations between marital satisfaction and controlling negative thoughts (r = 0.33), parenting stress (r = -0.40), and sexual satisfaction (r = 0.049) were significant (P < 0.01). In addition, the correlations between sexual satisfaction and controlling negative thoughts (r = 0.60) and parenting stress (r = -0.39) were also significant (P < 0.01). The relationship between the indirect path of controlling negative thoughts with marital satisfaction via the mediating role of sexual satisfaction was significant (β = 0.32, P = 0.010). Moreover, sexual satisfaction had a mediating role in the relationships between parenting stress and marital satisfaction in the parents (β = -0.08, P = 0.044). The results indicated a good fit of the model (IFI = 0.98, CFI = 0.96, RMSEA = 0.071). Conclusions: The results suggest that the proposed model had a good fit and could be considered an important step toward identifying the factors influencing the marital satisfaction of parents having children with learning disabilities.